Changing the way you teach, improving the way students learn - Martin-Kniep, Giselle O., 1956- (Association for Supervision and Curriculum Development, 2009)
Looking at curriculum design, assessment, and instructional practices, this book describes how teachers can optimize teaching and learning strategies no matter what grade level or subject they teach.